2020
DOI: 10.1002/anie.202008886
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alkynylallylation of the C−C σ Bond of Cyclopropenes

Abstract: AP d-catalyzed regio-and stereoselective alkynylallylation of as pecific C À C s bond in cyclopropenes,u sing allyl propiolates as both allylation and alkynylation reagents, has been achieved for the first time.B ym erging selective C(sp 2)-C(sp 3)b ond scission with conjunctive cross-couplings, this decarboxylative reorganization reaction features fascinating atom and step economy and provides an efficient approach to highly functionalizedd ienynes from readily available substrates.W ithout further optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Forthe efficient synthesis of 3u and 3v from cyclopropenes with electron-deficient double bond, the ligand P(p-CF 3 C 6 H 4 ) 3 needed to be replaced with ar elatively more electron-donating ligand P(2-furyl) 3 .T of urther confirm the structure of the products,w em easured the single crystals of 3j, 3u,a nd 3v,r espectively. [16] These results demonstrated that the selectivity of representative product 3jwas consistent with our inference from the model reaction and the s-bond selectivity of the reaction is not reversed by the enhance of steric effect (from 3uto 3v). It should be noted that some 1,1dicyanocyclopropenes cannot be smoothly used in this transformation even if the conditions were further optimized ( Figure 1).…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Forthe efficient synthesis of 3u and 3v from cyclopropenes with electron-deficient double bond, the ligand P(p-CF 3 C 6 H 4 ) 3 needed to be replaced with ar elatively more electron-donating ligand P(2-furyl) 3 .T of urther confirm the structure of the products,w em easured the single crystals of 3j, 3u,a nd 3v,r espectively. [16] These results demonstrated that the selectivity of representative product 3jwas consistent with our inference from the model reaction and the s-bond selectivity of the reaction is not reversed by the enhance of steric effect (from 3uto 3v). It should be noted that some 1,1dicyanocyclopropenes cannot be smoothly used in this transformation even if the conditions were further optimized ( Figure 1).…”
Section: Introductionsupporting
confidence: 86%
“…An acetonitrile solution of the substrates in the presence of 2.5 mol %P d 2 (dba) 3 and 15 mol %P ( p-CF 3 C 6 H 4 ) 3 at 70 8 8Cf urnished the desired product 3a in 88 %i solated yield (entry 1), and its structure was confirmed by single-crystal X-ray diffraction. [16] This model reaction exhibited outstanding chemo-, regio-, and stereoselectivity.N one of the other isomers had been found by the rough NMR or LC-MS testing.C ontrol experiments established the importance of P(p-CF 3 C 6 H 4 ) 3 (entries 2-4). Appropriate Pd to ligand ratio was critical for the efficient formation of the target molecule (entry 5).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Due to their unique properties caused by ring tension (about 54.1 kcal/mol), 1 cyclopropenes have been utilized as useful intermediates in organic synthesis. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 Consequently, many methods have been developed for their synthesis. 2–23 The carbene-transfer reaction between diazo compounds and alkynes has been among the most popular methods for the synthesis of cyclopropenes.…”
mentioning
confidence: 99%